Effects of Ultra-Low-Dose Aspirin in Thrombosis and Haemorrhage - Eizayaga, Francisco Xavier; Belon, Philippe; Desplat, Vanessa; Aguejouf, Omar; Doutremepuich, Christian (Homeopathy, 2019)
Background Aspirin is the oldest and possibly the most widely used pharmacologically active substance still used in allopathic medicine. Its effect on fever and inflammation has paved the way to its anti-thrombotic effect. Dilutions of aspirin have been tested for many years in the University of Bordeaux, in humans as well as in animal models.Methods This article is a review of the totality of articles published by the Laboratory of Hematology of the Faculty of Pharmacy of the University of Bordeaux, reporting different doses and dilutions of aspirin, different kinds of inhibitors, transgenic mice and animal models of disease such as portal hypertension and cirrhosis.Results Homeopathic dilutions of aspirin, notably 15 cH, have shown a pro-thrombotic effect in humans and in in-vivo animal studies. Longitudinal studies in rats have also shown an initial anti-thrombotic effect followed by a pro-thrombotic effect of aspirin several days after a single high-dose administration. This pro-thrombotic effect seems to act by inhibiting the cyclooxygenase (COX)-2 pathway in studies performed with COX selective inhibitors and in knock-out mice without COX-1 or COX-2. This effect may explain the thrombo-embolic complications described after aspirin withdrawal for the purposes of surgery or after non-compliance with anti-platelet therapy, and it may be beneficial in normalising primary haemostasis and decreasing haemorrhage in animal models of portal hypertension and cirrhosis.Conclusions Aspirin 15 cH acts through the inhibition of the COX-2 pathway producing a clear pro-thrombotic effect. Further studies should clarify if the pro-thrombotic effect of aspirin withdrawal and the effect of aspirin 15 cH are related, as secondary effects of the same drug. Clarifying this last outcome may be of great significance to public health.
Keywords: aspirin 15 cH; thrombosis; portal hypertension; homeopathy; COX inhibition; aspirin withdrawal